Report on business attachment Yaohan (S) Pte Ltd. - Quek, Seok Nee. (2009)
This report is written to describe the work done and things learned during the ten weeks of business attachment at Yaohan Singapore Pte Ltd. buring these ten weeks, one week each was spent at the Do-lt-Yourself and Furniture department of Yaohan Orchard and the remaining eight weeks were spent at the Yaohan Card Centre.